Formação inicial de professores do curso normal e recursos educacionais abertos: possibilidades e desafios para a prática profissional - Algarve, Fábia Lima (2021)
This research, linked to the line of research in networked educational technologies management of the Graduate Program in networked Educational Technologies at the Federal University of Santa Maria, in general, proposes to analyze the possibilities and challenges of the insertion of Open Educational Resources (OER) in teachers’ professional practice with the initial formation of the Normal Course - High School. Therefore, we list specific objectives a) Potentialize the construction of FTP through a workshop on OER; b) Analyze the teacher's work by building a reflection on its complexity and on its influence on pedagogical practice; c) Introduce ideas about the comprehension around the use of TDIC in teaching scope to teachers in initial training; d) Promote a workshop aiming at practical actions which enable the use and production of OER by teachers in initial training; e) Develop an e-book with the steps developed in the workshop. The theme represents a didactic-methodological proposal because it aims to enhance the construction of Technological-Pedagogical Fluency (TPF) through a training workshop for teachers in initial training of the Normal Course-High School, divided into 10 meetings, which approaches from teacher training to the production of didactic material in OER capable of assisting in pedagogical practice and teaching-learning process in the classroom. Developed in 4 months, between September 2019 and January 2020, the workshop followed a methodological path consisting of a cyclical research- action and data collection, through meetings and developed activities, observation records in a logbook and two semi-structured questionnaires, being one diagnostic questionnaire and the other evaluative. The theory-practice relationship is anchored in studies developed by Imbernón (2011), Alarcão (2011), Freire (2009), Vygotsky (2007), Mallmann; Schneider; Mazzardo (2013), Kenski (2008) and BNCC (2017) among othes, whose ideas based our journey throughout this research. Our results point to the challenges and possibilities of using Open Educational Resources (OER) in pedagogical practice and demonstrate the importance of the training process for the development of TPF and OER expansion. Cooperative and collaborative reflection was at the core of our research at the center of dialogical practice and reflects the changes in the teaching-learning process that may occur in each teacher involved in the research and in the training workshop. The elaborated E-book from workshop points to fundamental reflections and concerns for the understanding and use of OER and, in addition, enables the development of Technological-Pedagogical Fluency, as well as use of OER in teaching-learning of teachers in training initial.